STRATEGI BISNIS ONLINE DI BEKASI; KASUS PADA BISNIS CLOTING LINE - Budi Satria; Dhian Tyas Untari (Jurnal Ilmiah Akuntansi dan Manajemen, 2022)
This study aims to develop a clothing line online business strategy in Bekasi; Aspects of Marketing, Human Resources and Finance. The study involved 27 online and domiciled fashion clothing line entrepreneurs who are members of the Setu – Cilengsi MSME community. Data was collected through structured interviews related to aspects of marketing, Human Resources (HRD) and Finance and analyzed using EFAS IFAS and Grand Matrix. Based on the results of data analysis, the Clothing Line business in Bekasi is in the Matching Stage stage, the strategies chosen are market penetration strategy, product development strategy, backward integration strategy and horizontal integration.